Bagaimana Dampak Belanja Pemerintah dan Tingkat Investasi terhadap Pertumbuhan Ekonomi Regional di Kalimantan dan Sulawesi? - Lastri Susanti; Syahrituah Siregar (PPJP Universitas Lambung Mangkurat, 2023)
This research aims to (1) determine the effect of Government Expenditure and Investment Level on regional economic growth in Kalimantan and Sulawesi. (2) to find out how big the influence of each variable is and which variable is the most dominant influence of the variable Government Expenditure and Investment (DI and FI) on regional economic growth in Kalimantan and Sulawesi.This quantitative descriptive research uses the panel data regression analysis method using time series data from 2016 to 2020. Government spending, DI, FI, and economic growth are the variables used.The results of the study show that (1) Government Expenditures and the level of investment (domestic investment (DI) and foreign investment (FI)) together (simultaneously) have a significant effect on regional economic growth in Kalimantan and Sulawesi with the F-statistic test value of 0.003961. (2) Government spending and DI are the most dominant factors that have a positive and significant effect on regional economic growth in Kalimantan and Sulawesi, with probability t values of 0.0041 and 0.0506